2003
DOI: 10.1111/j.1748-5827.2003.tb00146.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐grade surface osteosarcoma in a dog

Abstract: A case of a high-grade surface osteosarcoma in the thoracic limb of a dog is reported. Radiographically, there was no bone involvement but there was increased soft tissue opacity. An aggressive osteosarcoma was diagnosed on the basis of early metastatic disease and histopathological examination. Previously reported surface osteosarcomas in the dog have been periosteal and parosteal osteosarcomas which are generally considered to have a low to intermediate biological activity. The tumour described here had radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In at least two cases of parosteal and one case of a high-grade surface OSA, metastatic disease was reported, though follow-up and staging are very variable amongst publications. 22,24,27 To the authors' knowledge, there are no previously reported canine cases of metastatic periosteal OSA. In our study, a relatively high proportion of dogs with surface OSA either had metastatic disease at the time of initial presentation…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In at least two cases of parosteal and one case of a high-grade surface OSA, metastatic disease was reported, though follow-up and staging are very variable amongst publications. 22,24,27 To the authors' knowledge, there are no previously reported canine cases of metastatic periosteal OSA. In our study, a relatively high proportion of dogs with surface OSA either had metastatic disease at the time of initial presentation…”
Section: Discussionmentioning
confidence: 97%
“…Typically, surface OSA is thought to be less biologically aggressive compared to central OSA 6 . The exception to this is high‐grade surface OSA that has been rarely reported in the dog 27 and humans 28…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pulmonary metastatic masses ranged from plain cartilagenous tissue to chondrosarcomatous changes in dogs and cats 4,8 . A case of canine high-grade surface osteosarcoma was histologically confirmed to have secondary pulmonary osteosarcomatous lesions despite the lack of radiographical evidence 9 . In this case no distant metastasis was observed radiologically in clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50 per cent of mammary tumours are malignant as discussed by Baba (2007) and they are considered to be the second most common tumour in dogs, after skin tumours , …”
Section: Classification Of the Stages Of Tumour Development [Source: mentioning
confidence: 99%